Probes of axial and nonaxial hexadecapole deformation effects in nuclei around 230U. (23rd February 2023) - Song, Zhuo; Wang, Hua-Lei; Zhang, Zhen-Zhen; Liu, Min-Liang
Abstract: The structure properties for even–even nuclei around 230 U, located on the hexadecapole-deformation island, are investigated using the potential-energy-surface calculation within the framework of the macroscopic−microscopic model. The impact of different deformation degrees of freedom (including axial and nonaxial quadrupole and hexadecapole deformations) on total energy, shell, and pairing contributions is analyzed, based on the projected energy maps and curves. The single-particle structure is presented and briefly discussed. To a large extent, a much better agreement with experimental data and other theoretical results is obtained if the hexadecapole deformations, especially the axial one, are taken into account. These results could provide useful insights into understanding the effects of different quadrupole and hexadecapole deformations.